Clarification of the taxonomic identity of the Himalayan species Thalictrum neurocarpum (Ranunculaceae), with the reduction of T. austrotibeticum to its synonymy - Yuan, Qiong; Ren, Chen; Yang, Qin-Er (Phytotaxa, 2018)
We demonstrate that Thalictrum neurocarpum (Ranunculaceae) is a distinctive species and readily distinguishable from T. reniforme by floral characters. We reduce T. austrotibeticum, recently described from southern Xizang (Tibet), China, to the synonymy of T. neurocarpum.